2014
DOI: 10.1186/2052-336x-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and health impacts of outdoor particulate matter in two urban and industrialized area of Tabriz, Iran

Abstract: Numerous studies have shown associations between air pollution and health effects on human. The aims of the present study were to provide quantitative data on variation of atmospheric particulate matter (PM) concentration and the impact of PM on the health of people living in Tabriz city. The approach proposed by the World Health Organization (WHO) was applied using the AirQ 2.2.3 software developed by the WHO European Centre for Environment and Health, Bilthoven Division. The concentration of particulate matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 33 publications
4
38
1
Order By: Relevance
“…Studies have shown a correlation between PM 2.5 mass and health end points -such as heart rate variability (HRV), blood neutrophils, and lipid changes (Tong et al, 2012) -increased oxidative DNA damage and nucleobases (Peter and Steffen, 2010), and cardiovascular mortality (Gholampour et al, 2014). The overall correlation between water-soluble DTT activity and PM 2.5 mass concentration observed in this study may help explain, at least in part, some of these associations.…”
Section: Oxidative Potential and Pm 25 Masssupporting
confidence: 52%
“…Studies have shown a correlation between PM 2.5 mass and health end points -such as heart rate variability (HRV), blood neutrophils, and lipid changes (Tong et al, 2012) -increased oxidative DNA damage and nucleobases (Peter and Steffen, 2010), and cardiovascular mortality (Gholampour et al, 2014). The overall correlation between water-soluble DTT activity and PM 2.5 mass concentration observed in this study may help explain, at least in part, some of these associations.…”
Section: Oxidative Potential and Pm 25 Masssupporting
confidence: 52%
“…The deviations between the obtained results and the above mentioned reported results by Engelbrecht et al are mainly due to the influence of temporal and spatial variation in PM ambient levels. However, our results are closer to the typical PM 2.5 /PM 10 ratio of 0.5 that have been documented for urban areas in developing countries [25], and reported for urban sites in Iran [26] . As shown in Table 6, very strong to moderate inter-correlations are found between PM of different size fractions.…”
Section: Pm Mass Ratiossupporting
confidence: 87%
“…Because, there is a great difference between Iran and Europe with regard to the age pyramid and the software's own default data are based on the European community, it cannot be used. Therefore by reviewing the relevant texts [9,10], we used the incidence and relative risks calculated for Iran. Tables 1-6…”
Section: Resultsmentioning
confidence: 99%